Tonsillar Microbiome‐Derived Lantibiotics Induce Structural Changes of IL‐6 and IL‐21 Receptors and Modulate Host Immunity. Issue 30 (28th August 2022) - Li, Jing; Jin, Jiayang; Li, Shenghui; Zhong, Yan; Jin, Yuebo; Zhang, Xuan; Xia, Binbin; Zhu, Yinhua; Guo, Ruochun; Sun, Xiaolin; Guo, Jianping; Hu, Fanlei; et al.
Abstract: Emerging evidence emphasizes the functional impacts of host microbiome on the etiopathogenesis of autoimmune diseases, including rheumatoid arthritis (RA). However, there are limited mechanistic insights into the contribution of microbial biomolecules especially microbial peptides toward modulating immune homeostasis. Here, by mining the metagenomics data of tonsillar microbiome, a deficiency of the encoding genes of lantibiotic peptides salivaricins in RA patients is identified, which shows strong correlation with circulating immune cells. Evidence is provided that the salivaricins exert immunomodulatory effects in inhibiting T follicular helper (Tfh) cell differentiation and interleukin‐21 (IL‐21) production. Mechanically, salivaricins directly bind to and induce conformational changes of IL‐6 and IL‐21 receptors, thereby inhibiting the bindings of IL‐6 and IL‐21 to their receptors and suppressing the downstream signaling pathway. Finally, salivaricin administration exerts both prophylactic and therapeutic effects against experimental arthritis in a murine model of RA. Together, these results provide a mechanism link of microbial peptides‐mediated immunomodulation. Abstract : The present study uncovers that the microbiome‐derived lantibiotics salivaricins directly act on IL‐6 and IL‐21 receptors and suppress  the abnormal activation of Tfh cell and overproduction of IL‐21, thus maintaining host immune homeostasis. The deficiency of salivaricins in the tonsillar microbiome of autoimmune diseases like rheumatoid arthritis may reduce the capacity for proper modulation of immune responses, thereby underlying autoimmune disorders.